Ministry of Tourism, Environment, Investment and Commerce - (:unkn) unknown (My University, 2011)
Mission Statement To develop effective policies aimed at maintaining a quality tourism industry in order to sustain a strong economy in which the residents of the Cayman Islands can continue to enjoy a high standard of living; to develop appropriate policies for the departments, units and statutory authorities for which the Ministry has responsibility in order to ensure they are efficiently managed and provide the service which their customers require.
Keywords: Tourism, Environment, Investment and Commerce